HERMES – a GUI‐based software tool for pre‐processing of X‐ray absorption spectroscopy data from laboratory Rowland circle spectrometers. (21st December 2021) - Seddon-Ferretti, Marco E.; Mottram, Lucy M.; Stennett, Martin C.; Corkhill, Claire L.; Hyatt, Neil C.
Abstract : HERMES is a graphical user interface software tool for pre‐processing X‐ray absorption spectroscopy data from laboratory Rowland circle spectrometers. Abstract : HERMES, a graphical user interface software tool, is presented, for pre‐processing X‐ray absorption spectroscopy (XAS) data from laboratory Rowland circle spectrometers, to meet the data handling needs of a growing community of practice. HERMES enables laboratory XAS data to be displayed for quality assessment, merging of data sets, polynomial fitting of smoothly varying data, and correction of data to the true energy scale and for dead‐time and leakage effects. The software is written in Java 15 programming language, and runs on major computer operating systems, with graphics implementation using the JFreeChart toolkit. HERMES is freely available and distributed under an open source licence.